Vocalise: definição, aplicação e função segundo professores de canto - Lima, Heloisa Evelyn Ferreira Carmo (2023)
Introduction: The term vocalise has different meanings; for certain authors is a composition, without text, sung under one or more vowels, for other authors is a vocal exercise usually used by singing teachers to improve the sound quality of their students' voices. The singing teachers use vocalises with their students in order to develop many skills. We know that the choice of a certain vocalise by the singing teacher is related to the development of specific skills. But how exactly does this relation occur? Objective: to analyze the definition, application and function of vocalises by singing teachers. Method: it’s about an analytical research, transverse, with a qualitative and quantitative character. The sample was composed of singing teachers with at least two years of professional performance. The questionnaire applied through the platform Google Forms was divided into two parts: characterization of the sample and investigation of the using and the function of vocalises. A pilot study has been carried out to verify the intelligibility of the instrument and the time of answer. The categorical analysis of Minayo was used and the keywords in the text were grouped by topics. Results: between 57 teachers investigated, 64.9% are women. The mean age was 38.1 years. 35 of the participants worked in the State of São Paulo (61.4%). Of the places where they work, 44 of the participants (77.2%) work in “a studio, their own environment or the student's home”. In the responses on definitions of vocalises, the term vocal exercises stands out, followed by syllabic exercises and melodic sequences. Regarding the application and function of vocalises, three categories were the most cited: vocal techniques (47.4%); vocal development (47.4%) and musicality (45.6%). Final Considerations: according to the sample of this research, vocalise is an exercise used to develop the student's voice, improve their musicality and apply different vocal techniques. The functions of the vocalises are directly related to the phonemes that compose it and the emission instructions from the singing teacher